Application of Good Logistics Practices to Export-Oriented SMEs through Export Regulation Applications - Miftahol Arifin; Ratih Windu Arini; Bachtiar Herdianto; Kania Putri Muliate (OPSI, 2022)
In penetrating exports, SME players are often faced with obstacles such as their unpreparedness in preparing the documents needed for exports. This problem is a classic problem considering that the ability to prepare export documents is a way to export successfully. Also, SME actors need to implement Good Logistic Practices (GLP) such as product processing activities, packaging, storage and shipping management to become resilient SMEs in line with the increasing understanding of export documents.  The approach used in this study is quantitative research methods with a study survey approach and normative empirical studies. Data analysis uses a correlation approach between variables. This study used data from 210 SMSs in the KUB Cilongok, with a sample of 71 respondents. The results of the study showed that 71.5% of SME players in penetrating the export market were still constrained in understanding export documents. So to achieve export capability, it is necessary to create a comfortable and balanced supply chain